Biometric Recognition 6th Chinese Conference, CCBR 2011, Beijing, China, December 3-4, 2011. Proceedings - Sun, Zhenan; Lai, Jianhuang; Chen, Xilin; Tan, Tieniu (Springer eBooks., 2011)
This book constitutes the refereed proceedings of the 6th Chinese Conference on Biometric Recognition, CCBR 2011, held in Beijing, China in December 2011. The 35 revised full papers were carefully reviewed and selected from 71 submissions. The papers are organized in topical sections on problems in face; iris; hand biometrics; speaker; handwriting; gait; behavioral and soft biometrics; and security.